Determinación de los parámetros de perforación para la mejora en la calidad del hueco mediante herramientas de fondo LWD, dinámica de perforación y configuración del BHA para la perforación de un pozo en la Cuenca de los Llanos Orientales. (2024)
This degree work allowed us to determine, using downhole tools, BHA configuration and drilling dynamics, the drilling parameters for improving hole quality. Firstly, it began with the generalities of the Eastern Plains Basin, where its historical overview and location is located. We continue with the theoretical framework where all the necessary information that gives context to the research is covered, starting with a description of the LWD tools, sensors, drilling dynamics, types of well profiles and giving greater strength to the drilling parameters. , BHA tools and types of drill bits. Secondly, the information was consolidated in order to identify the number of wells to be evaluated through data correlation.